1981
DOI: 10.1104/pp.67.5.958
|View full text |Cite
|
Sign up to set email alerts
|

β-Conglycinins in Developing Soybean Seeds

Abstract: The temporal sequence of development of the major proteins of seeds of soybean (Meff.) has been studied during development of cotyledons from flowering to maturity. A well-defrned difference occurred in the tmes of appearance and the periods of maximum accumulation of a-, a'-, and /8-subunits of betaconglycinin. Whereas a-and a'-subunits appeared 15 to 17 days after flowering, accumulation of ,8-subunit did not commence until 22 days after flowering. Such alterations in subunit composition infer that changes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
30
0

Year Published

1983
1983
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 14 publications
1
30
0
Order By: Relevance
“…f3-Conglycinin is a trimeric molecule of 180,000 to 240,000 D and is composed, primarily, of various combinations of the a', a, and # subunits (22), as well as lesser amounts of polypeptides related to a' and a-subunits that have been designated the y subunits (J Bryant, unpublished data). The a' and a subunits begin to accumulate soon after the cell division phase of seed development is completed (about 18 to 20 d after anthesis); the ,3 subunit accumulates 5 to 7 d later (8,17,21). The accumulation of j3-conglycinin mRNA molecules in seed was found to increase just prior to that of the protein subunits (9, 17).…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…f3-Conglycinin is a trimeric molecule of 180,000 to 240,000 D and is composed, primarily, of various combinations of the a', a, and # subunits (22), as well as lesser amounts of polypeptides related to a' and a-subunits that have been designated the y subunits (J Bryant, unpublished data). The a' and a subunits begin to accumulate soon after the cell division phase of seed development is completed (about 18 to 20 d after anthesis); the ,3 subunit accumulates 5 to 7 d later (8,17,21). The accumulation of j3-conglycinin mRNA molecules in seed was found to increase just prior to that of the protein subunits (9, 17).…”
mentioning
confidence: 93%
“…Using the developmental timetable presented in Table I, soybean embryos at specific developmental stages were selected and seed protein extracts were prepared. Seed proteins were extracted by homogenizing the immature seeds, fully mature dry seeds, or the radicle portion of the embryonic axes in 35 mm K-phosphate (pH 7.3), 10 (8,17,21). Meinke et al (17) also reported that the accumulation of each subunit differs in a tissue dependent manner.…”
mentioning
confidence: 99%
“…The genes encoding these three subunits are a11 expressed during the middle and latter stages of seed development. However, detailed analyses of subunit gene expression revealed variation in temporal (Gayler and Sykes, 1981; Meinke et al, 1981; Naito et al, 1988) and spatial (Ladin et al, 1987) pattems of expression during soybean seed maturation. Nutritional stresses of whole plants such as sulfate deficiency or potassium deficiency change the accumulation of the subunit proteins (Gayler and Sykes, 1985).…”
mentioning
confidence: 99%
“…Storage protein accumulation is expressed throughout the seed develop-ental stages. All the three subunit genes of the fl-conglycinin are expressed specifically at the middle to late stages of soybean seed development, although the expression of each subunit gene is regulated differently in terms of time and tissue specificity (Gayler and Sykes 1981;Meinke et al 1981;Ladin et al 1987;Naito et al 1988). …”
mentioning
confidence: 99%